Pathology and host-pathogen interactions in a golden Syrian hamster model of Nipah virus infection - Inés Ruedas-Torres; Stephen Findlay-Wilson; Emma Kennedy; Stuart Dowall; Francisco Javier Salguero (Frontiers in Veterinary Science)
Nipah virus (NiV) is recognized as one of the key pathogens with pandemic potential. We have recently established a NiV hamster model, which reproduces a highly similar disease to that observed in human cases, including respiratory and neurological signs and lesions. The aims of this study were to describe the microscopic lesions observed in the golden Syrian hamster model after intranasal (IN) and intraperitoneal (IP) inoculation with different doses of the Malaysian strain of NiV; to describe in depth the cell composition of the pulmonary and the brain lesions and the expression of proinflammatory cytokines in-situ using a combination of histopathological techniques including immunohistochemistry (IHC) and in-situ hybridisation (ISH) via RNAscope technique. We also developed a multiplex IHC which will allow us to study the interaction of the virus with cell populations in the lung and brain in future studies. For this, we selected 28 lung and brain formalin-fixed paraffin-embedded (FFPE) samples from previous experiments performed by our research group. Histopathology revealed severe pulmonary broncho-interstitial pneumonia, mainly in animals inoculated via the IN route, accompanied by a strong acute inflammatory response (Iba1+ cells) and high levels of NiV RNA. Upregulation of proinflammatory cytokines (IL-6 and TNF) was also observed by ISH RNAscope technique in these animals. Neurological lesions, consisting of perivascular cuffing and meningitis, were observed mainly in animals inoculated via IP route. IHC results showed astrocytosis (GFAP+) and microgliosis (Iba1+) in the brain of these animals, together with mild levels of IL6 and TNF mRNA. These results have helped us to characterize the host-pathogen interaction in the golden Syrian hamster animal model of NiV infection that is being currently used in preclinical testing of antiviral and vaccine strategies. Techniques used in this study could be applied to the development and application of golden Syrian hamster models of other infections by henipaviruses, including Hendra virus (HeV), and other high consequence priority pathogens.